STRATEGI PENGEMBANGAN WAHANA BERMAIN DI OBJEK WISATA KOLAM RENANG MALIBO ANAI PADANG PARIAMAN - Amelya, Rizki (journal of residu, 2019)
This research is motivated by the absence of playgrounds available at Malibo Anai Swimming Pool Attractions such as slides that are not available in the Malibo Anai Swimming Pool like other water attraction in West Sumatera. Visitor who come a lot want the Malibo Anai Swimming Pool Attraction to add more complete playgrounds equivalent to the Waterpark like the Fantasy Minang in Padang Panjang. This research is a descriptive study with qualitative data. Data collection techniques are carried out by using interviews, observation, and documentation methods. Determination of informants using Purposive Sampling techniques, namely with two managers, two people around the tourist attraction and two. The results of this study state that: 1) the strength of a tourist attraction Malibo Anai Swimming Pool is an area that is in the hills and close to the water source, and the uniqueness of the Swimming Pool Malibo Anai is a pool that is formed from natural stepping stones. The location is perfect for outbound, camping activities. Flying fox, jogging track, etc. 2) The weakness is the lack of attention from the manager to the security and safety of visitors in the pool 3) Opportunities owned by tourism objects are the increasing number of tourists visiting each year and the vast area of tourism that is quite exetensive can be developed. 4) The threat is the level of education and understanding of tourism objects by incompetent human resources so that tourism objects are not managed well. In addition, the surrounding community demands the management to empower employees from surrounding communities, although some of them have not yet been competent.